Pemikiran Mahbub Djunaidi Tentang Agama dan Politik Pada Tahun 1970-1995 - Ulfiyana Latifah; Agus Mulyana (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
Mahbub Djunaidi is a thinker figure from Nahdlatul Ulama. When he became a columnist in 1970-1995, many of his thoughts poured in the newspapers. In the article, Mahbub Djunaidi talked about things related to religious and political aspects. This study outlined the question “How was Mahbub Djunaidi’s thought about religion and politics in 1970-1995?” To answer the question, this study used historical methods which consist of the heuristic stage, source criticism, interpretation and historiography as well as the research technique of literature study and interviews with some relevant sources from the problems researched. Based on the results, it could be found that Mahbub Djunaidi was a columnist from the Nahdlatul Ulama circle which in his writing poured many thoughts on religion and politics. His thought towards religion in 1970-1995 discussed many things social life that can not be separated from Ahlussunnah Wal Jama’ah.Whilst his thought about politics discussed many things about the relationship betweenIslam and the state, as well as the relationship between Nahdlatul Ulama and thestate that can not be separated from the democracy school of thought. This research isexpected to be a reference for the next research, so it can present new facts that have notbeen revealed from this research.